Thomas Jay Oord’s Open and Relational Theology: Divine Sovereignty and Human Free Will - Sandjaja , Irawati; Octavianus , Jonathan; Juanda, Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
Open and Relational Theology, developed by Thomas Jay Oord, presents a controversial theological paradigm that emphasizes God’s openness and human free will as determinative factors for the future. This concept challenges traditional understandings of divine sovereignty and foreknowledge. This study aims to critically analyze the theological foundations of Open and Relational Theology, examine its implications for the doctrine of God’s sovereignty, and evaluate its consistency with biblical hermeneutics. Employing a qualitative approach, this research utilizes doctrinal analysis and comparative literature review. Primary data consists of Thomas Jay Oord’s works and related systematic theological literature, while secondary data includes theological journals and academic critiques of Open Theism. The findings reveal that Oord’s Open and Relational Theology constructs a mutual and interdependent God-human relationship, wherein divine foreknowledge is limited by human free will. This concept implies an indeterministic and probabilistic future, which stands in contrast to the doctrine of divine sovereignty in orthodox theology. Hermeneutical analysis uncovers inconsistencies with the biblical narrative of God's sovereign plan. Although Oord’s Open and Relational Theology offers a potential solution to the problem of theodicy, it fundamentally weakens the concept of divine sovereignty and introduces the risk of theological relativism in scriptural interpretation. Its practical implications may significantly alter the foundations of orthodox Christian faith.